Characterization of Pectoralis Major Muscle Satellite Cell Population Heterogeneity, Macrophage Density, and Collagen Infiltration in Broiler Chickens Affected by Wooden Breast - Ferreira, Tamara Z.; Kindlein, Liris; Flees, Joshua J.; Shortnacy, Lauren K.; Vieira, Sergio L.; Nascimento, Vladimir P.; Meloche, Kathryn J.; Starkey, Jessica D. (Frontiers in Physiology, 2020)
Muscle satellite cells (MSC) are myogenic stem cells that play a critical role in post-hatch skeletal muscle growth and regeneration. Activation of regeneration pathways to repair muscle fiber damage requires both the proliferation and differentiation of different MSC populations as well as the function of resident phagocytic cells such as anti-inflammatory and pro-inflammatory macrophages. The Wooden Breast (WB) phenotype in broiler chickens is characterized by myofiber degeneration and extensive fibrosis. Previous work indicates that the resident MSC populations expressing the myogenic regulatory factors, Myf-5 and Pax7 are larger and more proliferative in broilers severely affected with WB vs. unaffected broilers. To further characterize the cellular and molecular changes occurring in WB-affected muscles, samples from pectoralis major (PM) muscles with varying severity of WB (WB score 0 = normal; 1 = mildly affected; 2 = severely affected) were collected at 25 and 43 d post-hatch (n = 8 per score per age) and processed for cryohistological and protein expression analyses. Collagen per field and densities of macrophages and MyoD+, Myf-5+, and Pax7+ MSC populations were quantified on immunofluorescence-stained cryosections. Relative collagen protein expression was quantified by fluorescent Western Blotting. In both 25 and 43-d-old broilers, the proportion of collagen per field (P ≤ 0.021) and macrophage density (P ≤ 0.074) were greater in PM exhibiting severe WB compared with normal. At d 43, populations of MyoD+, Myf-5+:MyoD+ MSC were larger and relative collagen protein expression was greater in WB-affected vs. unaffected broilers (P ≤ 0.05). Pax7+ MSC relative to total cells was also increased as WB severity increased in 43-d-old broilers (P ≤ 0.05). Densities of Myf-5+ (P = 0.092), MyoD+ (P = 0.03), Myf5+:MyoD+ (P = 0.046), and Myf-5+:MyoD+:Pax7+ (P = 0.048) MSC were greater in WB score 1 birds compared with WB score 0 and 2 birds. Overall, alterations in the resident MSC and macrophage populations and collagen protein content were observed in WB-affected muscle. Further investigation will be required to determine how these changes in cell population kinetics and local autocrine and paracrine signaling are involved in the apparent dysregulation of muscle maintenance in WB-affected broilers.